Effectiveness Of Virtual Agricultural Channels Broadcasted Through Youtube As Perceived By The Farmers - Pervin, Shahnaj; Ahmed, Mohammad Bashir; Islam, Md. Matiul; Khatun, Mahfuza (New Countryside, 2025)
YouTube is one of the most widely used social media platforms for accessing agricultural information, general news, and entertainment. This study aimed to assess farmers’ perceptions of the effectiveness of virtual agricultural channels broadcasted through YouTube in Dumuria Upazila, Khulna District, Bangladesh. Data were collected from 80 respondents using a snowball sampling technique through personal interviews conducted between August 25, 2022, and February 27, 2023 using an interview schedule. Information on farmers’ perceptions gathered, and ten popular YouTube channels were selected for evaluation. Descriptive statistics were used for data analysis, while Spearman’s rank correlation coefficient measured the relationships between independent and dependent variables. The findings revealed that 86.25% of respondents perceived virtual agricultural channels on YouTube as less effective overall. However, individual channel evaluations indicated that Shykh Seraj and Math Krishi were considered highly effective, whereas Agamir Krishi and Krishi Bioscope were perceived as less effective. Among the 13 characteristics analyzed, education, extension media contact, knowledge of virtual agricultural channels, contact with other virtual media, and extent of exposure to YouTube-based agricultural content showed a positive significant relationship with perceived effectiveness. Conversely, age, family size, and farming experience demonstrated a negative significant relationship. The primary challenge limiting the effectiveness of these virtual channels was the high cost and inaccessibility of required materials (77.5%), while the least common issue reported was the accuracy of information (52.5%). These findings highlight the need to enhance the accessibility, affordability, and reliability of YouTube-based agricultural content to better support farmers in Bangladesh.